Divergent, Regio- and Stereoselective Route for Aryl Sulfones from Morita–Baylis–Hillman Acetates - Saikia, Pranjit; Khom, Sonam Tashi; Sharma, Nabin; Yadav, Nagendra Nath (Synthesis, 2025)
A divergent route for regio- and stereoselective synthesis of aryl sulfones was reported from the reaction of Morita–Baylis–Hillman acetates with sodium sulfinate in the presence of DABCO as a hindered nucleophilic base. This is the first report that describes the formation of both α-substituted and γ-substituted (SN2′-substituted) products selectively under controlled reaction. This route furnished the expected aryl sulfone in good to excellent yields in a very short reaction time with high regio- and stereoselectivity.
Keywords: Baylis–Hillman acetates; DABCO; Arylsulfinate; Allyl sulfones; Stereoselective synthesis; α-substitution and SN2′ substitution